Analisis Peran Partai Golkar Kota Serang dalam Penyusunan dan Pengawalan Perda Penyelenggaraan Usaha Kepariwisataan melalui Teori Institutional Analysis and Development - Juwita Siregar; Modella Raghel Monika; Aulia Putri Nadifa; Natasya Melinda Puspita (Jurnal Hukum dan Sosial Politik, 2025)
This study analyzes the role of the Golkar Party of Serang City in the formulation and oversight of Regional Regulation Number 11 of 2019 on the Implementation of Tourism Business Governance using the Institutional Analysis and Development (IAD) framework. The study aims to examine how political party institutions perform their functions in local legislative processes, particularly in terms of public representation, interest articulation, and policy oversight. A qualitative case study approach was employed, involving in-depth interviews with party actors and members of the Regional House of Representatives (DPRD), as well as document analysis of relevant policy materials. The findings reveal that Golkar’s role in the formulation and supervision of the regulation was predominantly carried out by its legislative faction through informal mechanisms, while the party’s organizational structure played a limited institutional role. The process of absorbing public aspirations was relatively constrained and tended to favor groups with close social and political ties, indicating that the party has not fully exercised its functions of public articulation and accountability. From the perspective of the IAD framework, this condition reflects weaknesses in internal rules, actor capacity, and interaction mechanisms within the party as a political institution in the policy arena. Therefore, strengthening Golkar’s institutional capacity is essential to enable a more substantive, responsive, and inclusive role in local legislative and policy oversight processes